Perception of oral health and oral health-related quality of life among aviators in the armed forces: A cross-sectional study - Srihari Krishna Kaushik; Adil Farzand; Harikrishnan Venkatakrishnan (Indian Journal of Aerospace Medicine, 2026)
Objectives: Oral health significantly influences functional performance and psychological well-being. Military aviators operate under unique physiological and operational stresses where even minor dental issues can compromise in-flight performance and safety. As evidence regarding oral health-related quality of life (OHRQoL) among military aviators is scarce, this study aimed to assess the perception of oral health and OHRQoL using the Oral Health Impact Profile-14 (OHIP-14) and to evaluate its association with demographic, occupational, and behavioral factors. Material and Methods: A cross-sectional study was conducted among 430 military aviators using a structured, self-administered online questionnaire comprising flying attributes, demographic details, oral health awareness and hygiene habits, smoking habits, and the validated OHIP-14 instrument. Descriptive statistics, unpaired t -tests, one-way analysis of variance, and Spearman’s correlation were performed using IBM Statistical Package for the Social Sciences version 26.0, with significance set at p < 0.05. Results: Overall OHRQoL among aviators was favorable. Functional limitation (mean = 4.10 ± 1.89) and physical pain (mean = 2.22 ± 1.59) were the most affected domains. Advancing age and longer service duration were significantly associated with higher OHIP scores ( p < 0.001). Smokers demonstrated significantly poorer OHRQoL compared to non-smokers ( p = 0.047). Strong positive correlations were observed among physical pain, functional limitation, physical disability, and handicap domains. Conclusion: Aviators demonstrated favorable OHRQoL; however, functional limitation and physical pain remain key concerns. Age, duration of service, and smoking were major determinants of reduced OHRQoL. Incorporating periodic OHRQoL assessments, smoking cessation counseling, and preventive oral health programs into aeromedical evaluations can enhance dental readiness and operational efficiency in the Armed Forces.